Pengaruh Latihan Ankle Weight dan Karet Terhadap Kecepatan Tendangan Dollyo Chagi Atlet Taekwondo Samin Blora - M Ali Furqon; Bambang Priyono (Indonesian Journal for Physical Education and Sport, 2023)
The purpose of this study was to determine the effect of the ankle weight training model and rubber tensile load on increasing the ability of dollyo chagi kick speed in Taekwondo athletes at the TSB club, Blora Regency. Using the experimental method with the Pretest-Posttest Control Group. The results showed that: (1) The results of the t-test of ankle weight weight training were known to have sig. (2-tailed) was 0.001 <0.05 and the rubber weight training was sig. (2-tailed) of 0.003 <0.05, which means that there is an effect. (2) The results of the test of the difference in the effect between ankle weight and rubber weight training on dollyo chagi kick speed are seen from the Mean Difference value which shows that exercise using ankle weight weights has a more significant effect than exercise using rubber weights. Mean Difference (bending load). 51%> rubber load 49%). It can be concluded that ankle weight training has a more significant effect than rubber weight training to increase kick speed.